2014
DOI: 10.1016/j.canlet.2013.08.037
|View full text |Cite
|
Sign up to set email alerts
|

MiR-203 suppresses tumor growth and invasion and down-regulates MiR-21 expression through repressing Ran in esophageal cancer

Abstract: The expression of miR-203 has been reported to be significantly down-regulated in esophageal cancer. We showed here that overexpression of miR-203 in esophageal cancer cells dramatically increased cell apoptosis and inhibited cell proliferation, migration and invasion as well as tumor growth and down-regulated miR-21 expression. We subsequently identified that small GTPase Ran was a target gene of miR-203. Furthermore, Ran restoration partially counteracted the tumor suppressive effects of miR-203 and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 30 publications
3
54
1
1
Order By: Relevance
“…In particular, miR-203 is defined as a tumor suppressor for controlling EMT and metastasis in several cancers (Davis et al, 2006;Mega et al, 2005;Moes et al, 2012;Saini et al, 2011;Zhang et al, 2014;Zhang et al, 2011). Additionally, various research groups studying miRNA expression profiles have revealed that miR-203 decreases in esophageal cancer (Feber et al, 2008;Mathé et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, miR-203 is defined as a tumor suppressor for controlling EMT and metastasis in several cancers (Davis et al, 2006;Mega et al, 2005;Moes et al, 2012;Saini et al, 2011;Zhang et al, 2014;Zhang et al, 2011). Additionally, various research groups studying miRNA expression profiles have revealed that miR-203 decreases in esophageal cancer (Feber et al, 2008;Mathé et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer contains two histological types, esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) [2]. In China, a high incidence of ESCC exceeds 100 cases per 100,000 people per year.…”
Section: Introductionmentioning
confidence: 99%
“…Down regulation of miR-203 expression was found in several types of cancers, including gastric cancer [8], hepatocellular carcinoma (OS) [9], non-small cell lung cancer (NSCLC) [10], cervical cancer [11], esophageal cancer [12] as well as melanoma [13]. However, studies also showed that miR-203 was up regulated in breast cancer [14], colorectal cancer [15], ovarian cancer [16] and pancreatic adenocarcinoma [17].…”
Section: Introductionmentioning
confidence: 99%